Pengaruh Akuntabilitas, Pengendalian Internal, dan Ketaatan Aturan Akuntansi terhadap Kecenderungan Kecurangan Akuntansi (Studi Kasus pada Pemerintah Daerah Kabupaten Gresik) - Riesma Carunia Firdausy; Rida Perwita Sari (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine the effect of accountability, internal control, and obedience to accounting rules on the tendency of accounting fraud in the local government in Gresik Regency. This study uses quantitative methods by using primary data sources through questionnaires. The variable measurement technique uses a Likert scale of 1-5. The population of this study were 26 agencies and offices in Gresik Regency. The sample of this research used purposive sampling method. The results showed that accountability and internal control had a significant effect on the tendency of accounting fraud. Meanwhile, obedience to accounting rules has no significant effect on the tendency of accounting fraud.